Intention to Use Instagram by Generation Cohorts: The Perspective of Developing Markets - Hiram, Ting; Ernest Cyril, de Run; Siew, Ling Liew (Global Business and Management Research, 2016)
Purpose: The study aims to investigate the effect of behavioural and normative beliefs on attitude and subjective norm towards the use of Instagram respectively, and subsequently their effect on intention to use Instagram by generation cohort. The theory of reasoned action is adopted as underlying basis to explain the relationships under investigation. Design/methodology/approach: The study was conducted in Sarawak, an emerging market in Malaysia and Southeast Asia. 405 respondents were sampled using purposive sampling technique. They were grouped based on Sarawakian cohorts, rather than the cohorts from the U.S. sources. Data was collected through self-administered questionnaire and analyzed using multiple regressions and ANOVA. Findings: The findings show that behavioural and normative beliefs partially affect attitude and subjective norm towards the use of Instagram respectively. However, both attitude and subjective norm are significant predictors of intention to use. Additionally, the older cohort is found to rely more on opinions of significant others than the younger cohorts when considering the use of Instagram. Originality/value: - Although Instagram is gaining great popularity in contemporary society, little has been done to investigate user behaviour towards the application by generation cohorts in the context of developing markets. The study articulates the implication of generational impact on Instagram usage, thus articulating the antecedents of usage across generation cohorts.